Antiviral effect of the viroporin inhibitors against Taiwan isolates of infectious bronchitis virus (IBV) - Sitinjak, Mikael Cristofer; Chen, Jui-Kai; Liu, Fang-Lin; Hou, Ming-Hon; Lin, Shan-Meng; Liu, Hung-Jen; Wang, Chi-Young (Virus research, 2024)
•The envelope (E) proteins of infectious bronchitis virus (IBV) resulted in inhibited bacteria growth, increased permeability of bacteria, and blocked protein synthesis of bacteria.•Hygromycin B impeded protein translation in DF-1 cells and damaged their membrane integrity in the presence of E proteins.•The viroporin activity of the E proteins from IBV H-120, IBV serotype TW-I, and IBV serotype TW-II was confirmed.•Treatments with the viroporin inhibitors increased the survival rates in IBV-infected chicken embryos and chickens.•Viroporin inhibitors bound to the lipid-facing surface within the transmembrane domain of the E protein, inhibiting ion conduction. Coronaviruses (CoVs) are significant animal and human pathogens, characterized by being enveloped RNA viruses with positive-sense single-stranded RNA. The Coronaviridae family encompasses four genera, among which gammacoronaviruses pose a major threat to the poultry industry, which infectious bronchitis virus (IBV) being the most prominent of these threats. Particularly, IBV adversely affects broiler growth and egg production, causing substantial losses. The IBV strains currently circulating in Taiwan include the IBV Taiwan-I (TW-I) serotype, IBV Taiwan-II (TW-II) serotype, and vaccine strains. Therefore, ongoing efforts have focused on developing novel vaccines and discovering antiviral agents. The envelope (E) proteins of CoVs accumulate in the endoplasmic reticulum-Golgi intermediate compartment prior to virus budding. These E proteins assemble into viroporins, exhibiting ion channel activity that leads to cell membrane disruption, making them attractive targets for antiviral therapy. In this study, we investigated the E proteins of IBV H-120, as well as IBV serotypes TW-I and TW-II. E protein expression resulted in inhibited bacteria growth, increased permeability of bacteria to β-galactosidase substrates, and blocked protein synthesis of bacteria by hygromycin B (HygB). Furthermore, in the presence of E proteins, HygB also impeded protein translation in DF-1 cells and damaged their membrane integrity. Collectively, these findings confirm the viroporin activity of the E proteins from IBV H-120, IBV serotype TW-I, and IBV serotype TW-II. Next, the viroporin inhibitors, 5-(N,N-hexamethylene) amiloride (HMA) and 4,4’-diisothiocyano stilbene-2,2’-disulphonic acid (DIDS) were used to inhibit the viroporin activities of the E proteins of IBV H-120, IBV serotype TW-I, and IBV serotype TW-II. In chicken embryos and chickens infected with IBV serotypes TW-I and IBV TW-II, no survivors were observed at 6 and 11 days post-infection (dpi), respectively. However, treatments with both DIDS and HMA increased the survival rates in infected chicken embryos and chickens and mitigated histopathological lesions in the trachea and kidney. Additionally, a 3D pentameric structure of the IBV E protein was constructed via homology modeling. As expected, both inhibitors were found to bind to the lipid-facing surface within the transmembrane domain of the E protein, inhibiting ion conduction. Taken together, our findings provide comprehensive evidence supporting the use of viroporin inhibitors as promising antiviral agents against IBV Taiwan isolates.